New Characterization for Nonlinear Weighted Best Simultaneous Approximation. (10th August 2009) - Luo, Xianfa; Wu, Delin; He, Jinsu
Abstract : This paper is concerned with the problem of a wide class of weighted best simultaneous approximation in normed linear spaces, and it establishes a new characterization result for the class of approximation by virtue of the notion of simultaneous regular point.